Psychological health and subjective perception of happiness in mental disorders - Maruta, Oksana S. (Psychiatry, Neurology and Medical Psychology, 2021)
The aim of the study was to study psychological health (PH) and its relationship with subjective perception of happiness in patients with various types of mental disorders (MD). The set of research methods included the methodology “Individual model of psychological health”, “Semantic diff erential of happiness” (SDH) and methods of statistical processing of the data obtained. The study involved 210 patients with MD (70 with organic disorders, 70 with depressive disorders and 70 with neurotic disorders). It was found that with all variants of MD, a signifi cantly lower level of realizability of the “Prosocial” vector was determined, which refl ects the presence of internal and social coherence of the individual. In neurotic disorders, apart from Prosocial, the “Strategic” and “Family” vectors were also signifi cantly less realizable, which refl ected signifi cantly lower levels of family well-being, the ability for strategic planning, purposeful functioning, and persistence of these patients. In depressive disorders, the “Strategic”, “Intellectual” and “I” vectors were also signifi cantly less realizable, determining the low realizability of patients in this group, primarily in the spheres “I”-Realization, — emotional, intellectual, social and physical. In organic disorders among the components of the PH, the “Intellectual” vector was also less realized in comparison with the healthy group; The data obtained indicate that the subjective perception of happiness by patients with MD is associated primarily with the “Strategic”, “Prosocial”, “Family”, “Intellectual” and “I” vectors of the PH. The “creative”, “Spiritual” and “Humanistic” components of PH did not fi nd a relationship with the level of subjective perception of happiness in patients with MD.